Maternal Dietary Patterns during Pregnancy Are Associated with Child Growth in the First 3 Years of Life. Issue 11 (28th September 2016) - Martin, Chantel L; Siega-Riz, Anna Maria; Sotres-Alvarez, Daniela; Robinson, Whitney R; Daniels, Julie L; Perrin, Eliana M; Stuebe, Alison M
Abstract: Background: Child obesity is a major problem in the United States. Identifying early-life risk factors is necessary for prevention. Maternal diet during pregnancy is a primary source of fetal energy and might influence risk of child obesity. Objective: We prospectively investigated the influence of maternal dietary patterns during pregnancy on child growth in the first 3 y of life in 389 mother–child pairs from the Pregnancy, Infection, and Nutrition study. Methods: Dietary patterns were derived with the use of latent class analysis (LCA) based on maternal diet, collected with the use of a food-frequency questionnaire at 26–29 wk gestation. Associations between maternal dietary patterns and child body mass index (BMI)–for-age z score and overweight or obesity were assessed with the use of linear regression and log-binomial regression, respectively. We used linear mixed models to estimate childhood growth patterns in relation to maternal dietary patterns. Results: Three patterns were identified from LCA: 1 ) fruits, vegetables, refined grains, red and processed meats, pizza, french fries, sweets, salty snacks, and soft drinks (latent class 1); 2 ) fruits, vegetables, baked chicken, whole-wheat bread, low-fat dairy, and water (latent class 2); and 3 ) white bread, red and processed meats, fried chicken, french fries, and vitamin C–rich drinks (latent class 3). In crude analyses, the latent class 3 diet was associated with a higher BMI-for-age z score at 1 and 3 y of age and a higher risk of overweight or obesity at 3 y of age than was the latent class 2 diet. These associations were not detectable after adjustment for confounding factors. We observed an inverse association between the latent class 3 diet and BMI-for-age z score at birth after adjustment for confounding factors that was not evident in the crude analysis (latent class 3 compared with latent class 2—β: −0.41; 95% CI: −0.79, −0.03). Conclusion: In this prospective study, a less-healthy maternal dietary pattern was associated with early childhood weight patterns.